Chorion Extract as a Recovering Agent for Blood Biochemical Indices in Rats with Experimental Burns - Subbota, N. P.; Scherbak, I. M. (Problems of Cryobiology and Cryomedicine, 2005)
There was studied the content of lipid peroxidation products (diene conjugates and malone dialdehyde) as well as antioxidant system activity (SOD, catalase activity) in blood serum at a combined chorion extract application (intramuscular injection+ biobandage) in rats with experimental burns. There was found the fall in TBA-active products content and increase in enzymes activity (SOD and catalase) in blood serum of rats with experimental burns, that resulted in antioxidant index rise.